2019
DOI: 10.1002/lsm.23072
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced laser surface ablation with an integrated photoacoustic imaging and high intensity focused ultrasound system

Abstract: Background and Objective Combined laser and ultrasound treatments have been found to have synergistic effects, which may be of particular note in dermatology. We aim to investigate the potential of this technology for dermatology through in vitro and ex vivo experiments. Methods In vitro tissue phantoms made of agar and tattoo ink and tattooed ex vivo chicken breast tissue were used. An integrated photoacoustic imaging and high intensity focused ultrasound (HIFU) system, using a 5‐ns tunable OPO laser system a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
2
10
1
Order By: Relevance
“…The USELT is based on our earlier developed PUT technology. The high selectivity, precision, and safety of PUT technology have been demonstrated in our previous studies 30‐33 . Our current in vivo study demonstrated that USELT utilizing laser pulses with a fluence of 8 mJ/cm 2 at 532‐nm wavelength and ultrasound bursts with a peak negative pressure of 1.3 MPa at 0.5 MHz were effective for thrombolysis (shown in Figures 3, 5 and 6.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The USELT is based on our earlier developed PUT technology. The high selectivity, precision, and safety of PUT technology have been demonstrated in our previous studies 30‐33 . Our current in vivo study demonstrated that USELT utilizing laser pulses with a fluence of 8 mJ/cm 2 at 532‐nm wavelength and ultrasound bursts with a peak negative pressure of 1.3 MPa at 0.5 MHz were effective for thrombolysis (shown in Figures 3, 5 and 6.…”
Section: Discussionsupporting
confidence: 66%
“…Note that USELT is based on the synergistic effect between the light pulse and the ultrasound burst. Strong cavitation will only be induced at the location where laser and ultrasound energy overlap and are properly synchronized 30 . Due to the low applied ultrasound energy intensity, ultrasound alone is not capable of producing cavitation on the vessel wall and surrounding tissues (shown in Figure 3, ultrasound only; Figure 4, ultrasound only; Figure 5d‐f; Figure 6, ultrasound only; Figure 7a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasonic imaging has been used to monitor dermatological tattoo complications [9,10]. In addition to laser ablation [11], ultrasound has also been experimentally applied for tattoo removal [12,13]. The high-intensity focussed ultrasound used for this purpose ablates the tissue in or near the transducer focus, irrespective of the presence of ink.…”
Section: Introductionmentioning
confidence: 99%